ASPERGER'S SYNDROME: A CASE REPORT - AJITHAKUMARI.G, (International Journal of Pharma and Bio Sciences, 2016)
Asperger syndrome was named for the Austrian doctor, Hans Asperger, who first described the disorder in 1944. Asperger syndrome is a type of pervasive developmental disorder.Pervasive developmental disorders are a group of conditions that involve delays in the development of many basic skills, most notably the ability to socialize with others to communicate and to use imagination. Objective: to define the syndrome, its etiology, management and prognosis. Method: describing the symptomatology, etiology and proposed pathogenesis of the syndrome. Result: a case of age 11 years bought by his mother who was concerned that he was being bullied and teased at school. He was a poor mixer with other children and finally diagnosed to have Asperger syndrome and was treated for it. Conclusion: Asperger syndrome is not a mental illness. It is a developmental disorder affecting communication, social relationships and social imaginations. Everyone with Asperger syndrome is unique. Some are able to cope better than others in some areas of their life at different times in their life.